Effects of Colony Breeding System and Nest Architecture on Soil Microbiome and Fertility in the Fungus-Growing Termite Macrotermes barneyi Light - Zhou, Jiachang; Qin, Wenquan; Zeng, Yang; Huang, Xin; Yuan, Jing; Yin, Yuting; Xu, Paike; Fan, Xiaohong; Zhang, Runfeng; Li, Ganghua; Zhang, Yinqi (Insects (Basel, Switzerland), 2025)
Macrotermes barneyi is a typical fungus-growing termite that forms both monogynous (single queen) and polygynous (multiple queen) colonies in nature. This species influences the local soil fertility in part by redistributing nutrients across the landscape in its habitats. However, how the colony structure of M. barneyi affects nutrient cycling and microbial communities within the nest is not well understood. In this study, we compared the physicochemical properties and microbial communities across nest parts between monogynous and polygynous colonies of M. barneyi. Our results showed that the fungus garden is the most nutrient-rich part of the nest, with higher soil moisture, organic matter, ammonium nitrogen, nitrate nitrogen, available sulfur, available potassium, available silicon, and available boron than other nest parts. Notably, the fungus garden in monogynous colonies had higher nitrate nitrogen, available sulfur, and available silicon than those in the polygynous colonies. The microbial α-diversity in the fungus garden was lower than that in other parts of the nest. β-diversity analysis revealed a clear separation of microbial communities between monogynous and polygynous colonies across nest parts. Furthermore, the relative abundance of functional genes associated with “cell cycle control, cell division, and chromosome partitioning” was higher in the fungus garden of polygynous colonies compared to monogynous colonies. Our results suggest that the fungus garden plays a crucial role in maintaining colony stability in M. barneyi colonies. The rapid depletion of nutrients in the fungus garden to sustain the larger population in polygynous colonies likely influences microbial community dynamics and nutrient cycling.